Power Electronics for Domestic Induction Heating: a Review (2013)
This work presents a technical review about the development of the domestic induction heating systems. Initially, this paper presents basic concepts and general principles of induction heating and it focuses in the particular characteristics for domestic appliances and specifically in the power electronics. It shows the operation principles, the topologies of resonant inverter most used (serial, parallel, hybrid, quasi-resonant, and single-switch), the switching strategies, the control strategies using frequency modulation, width modulation, and pulse density, and the switching methodologies (soft and hard). Finally, it is done a brief analysis on the areas where further research is still needed such as multiple-outputs induction heating systems, single switch inverter topologies, and quasiresonant inverters.